2010
DOI: 10.14195/1647-8614_44-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de excelencia docente en la Universidad de Granada

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos.Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The sample can be characterized as follows: the participating subjects are mostly female, aged between 51 and 60 years, with 8 to 15 years of teaching seniority, with a permanent contract and full time, and are located in the field of social sciences. The inventory of perceptions about university teaching, to study teaching excellence, was developed and validated, analyzing its psychometric properties in the first [50] and successive applications. It was subsequently contextualized, translated into other languages, refined, and used to carry out different complementary studies in Spain, Brazil, Cuba, Mexico, and Canada [51][52][53][54][55][56].…”
Section: Sample Of the Descriptive/correlational Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The sample can be characterized as follows: the participating subjects are mostly female, aged between 51 and 60 years, with 8 to 15 years of teaching seniority, with a permanent contract and full time, and are located in the field of social sciences. The inventory of perceptions about university teaching, to study teaching excellence, was developed and validated, analyzing its psychometric properties in the first [50] and successive applications. It was subsequently contextualized, translated into other languages, refined, and used to carry out different complementary studies in Spain, Brazil, Cuba, Mexico, and Canada [51][52][53][54][55][56].…”
Section: Sample Of the Descriptive/correlational Phasementioning
confidence: 99%
“…The qualitative data analysis software Atlas.ti (28.0) was used for coding. In our study, we sought to identify and contrast the perspectives and trends of change indicated by the participants of the group considered as a whole [50,[59][60][61].…”
mentioning
confidence: 99%
“…En España la atención a la calidad y la excelencia docente se ha visto impulsada especialmente a partir del inicio del proceso de convergencia hacia un Espacio Europeo de Educación Superior, de aquí que a partir del año 2000 se hayan visto multiplicadas las publicaciones al respecto, especialmente sobre la cuestión más amplia de calidad y del buen docente universitario (Casero, 2010;Fernández-Cruz y Romero, 2010;García-Gallego et al, 2015;Gargallo et al, 2010;Hamer, 2015;Miguel, 2003;Monereo y Domínguez, 2014;Reyero, 2014;Villa, 2008). En México la literatura acerca de la buena docencia, la docencia de calidad o las buenas prácticas del docente universitario es también vasta (por ejemplo, Carlos, 2011;García y Medécigo, 2014;Luna, Valle y Osuna, 2010;Patiño, 2015;Rocha, 2012Rocha, , 2013.…”
Section: Sobre La Buena Docencia Universitaria Y La Atención a La Invunclassified
“…Por el contrario, es bastante escasa la investigación sobre la formación de los profesores ordinarios. Sin embargo, algunos autores (Villar, 1990;Fernández Cruz, 1999) han señalado las finalidades que, en relación con las necesidades educativas especiales, la formación del profesorado debe atender: Formación del profesor en el campo específico de las necesidades educativas especiales.…”
Section: ¿Formación Específica Para El Profesor Generalista?unclassified